Impact of beam–beam effects on absolute luminosity calibrations at the CERN Large Hadron Collider - Babaev A. A. Anton Anatoljevich; Barklow T.; Karacheban O.; Kozanecki, W.; Kralik I. (2024, 2024)
Title screen